Valorisation of By-Products from Soybean (Glycine max (L.) Merr.) Processing - Colletti, Alessandro; Attrovio, Andrea; Boffa, Luisa; Mantegna, Stefano; Cravotto, Giancarlo (Molecules (Basel, Switzerland), 2020)
In recent years, increased awareness of the health benefits associated with consuming soy-based foods, knowledge of milk-related allergies and a move towards more sustainable food production have led to an increase in the number of available soy-based products. The biggest producers in the world, the USA, South America and China, are from the Pacific region. This enormous production is accompanied by the accumulation of related by-products, in particular, a substance that is known as okara. Okara is a paste that is rich in fibre (50%), protein (25%), fat (10%), vitamins and trace elements. Its proper use would lead to economic advantages and a reduction in the potential for polluting the environment. Its high fibre content and low production costs mean that it could also be used as a dietary supplement to prevent diabetes, obesity and hyperlipidaemia. Chemical or enzymatic treatment, fermentation, extrusion, high pressure and micronisation can all increase the soluble fibre content, and thus improve nutritional quality and processing properties. However, the product also degrades rapidly due to its high moisture content (70–80%), which makes it difficult to handle and expensive to dry by conventional means. The aim of this paper is therefore to thoroughly study the existing literature on this subject in order to develop a general protocol for okara exploitation and valorisation. A cost/benefit analysis could drive the design of eco-friendly, sustainable protocols for the preparation of high-value nutritional products.